The Legal Protection of Homeworkers in The Perspective of Labor Copyright Law & Its Implementing Regulations - Nuradi, Nuradi; Wijaya, Mustika Mega (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Law No. 6 of 2023 was recently enacted in the hope of creating wider employment opportunities amidst intense global competition and the demands of economic globalization. The law regulates various aspects that aim to facilitate job creation through ease, protection, and empowerment for cooperatives and micro, small, and medium enterprises. In addition, the law also focuses on improving the investment ecosystem and accelerating the implementation of national strategic projects, and aims to improve the protection and welfare of home-based workers. For this reason, despite all the pros and cons of the issuance of Law Number 6 Year 2023 and its implementing regulations, it is recommended that the Government issue a regulation that specifically provides legal protection to homeworkers. The formulation and implementation of such a regulation should include the introduction and understanding of homeworkers as formal workers as well as informal workers; the policy direction of empowering homeworkers; the expansion of social protection for homeworkers; the development of homeworking and homeworkers as potential actors of micro and small businesses; and promoting the importance of gender equality and non-discrimination in the industrial relations between homeworkers and the parties. This research uses a normative juridical analysis approach. The results of this study found that in this context, the introduction, protection and empowerment of homeworkers and the development of homeworking can be one of the job creation strategies based on the real potential of the community economy that has been growing for a long time along with the development of an increasingly educated, advanced and innovative society.